Organic Solar Photovoltaic Cells: Synthesis of Indium Tin Oxide using Sol-Gel Method - Shanmuga Priya, S; Ruts, Stijn; Krishna Bandaru, SVSR (International Journal of Engineering and Technology, 2018)
Solar cells are a solution for the demand for clean and non-pollutant energy. The first two generations of solar cells were costly and bulky, or with rare metals. The third generation are thin films with a polymer or natural dye as active layer. The active layer materials are common in use and non-polluting. A side for the active layer, other layer must be implanted to make the circuit complete and let electrons flow trough. This work focusses on the production of Indium Tin Oxide (ITO) which act as a transparent conductive electrode.Â  The ITO will be placed in a dye-sensitized solar cell consisting of DNA-chlorophyll active layer. The focus is on the production process of the ITO using the sol-gel method. The precursors that are used are InCl3, SnCl4 and NH3 solutions. To obtain the sols for thin film preparation, the Sn-doped indium hydroxide needs to be dialyzed, aged, and dispersed in ethanol. Then calcination has to be done for preparing proper ITO. When spin coated in to a thin film characterisation can be done like X-ray diffraction, scanning electron microscopy and UV-Vis and near IR spectroscopy. The thin film can be placed in a DNA-chlorophyll as an active layer. After reviewing the simple structure of electrodes and active layer, some hole transmitting layers or electron transmitting layers to reduce the losses. The overall solar cell can be tested and the efficiency will be determined.Â